PEMANFAATAN LIMBAH KACA LAMPUSEBAGAI MEDIA PERALATAN PRAKTIKUM UNTUK PEMBELAJARAN KIMIA - Itsnaini Rahmawati, Yuni Nurfiana, Izzatin Kamala, Arif Hidayat, dan Friyatmoko W. K. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research is aimed at finding out the making process, the performance andsuitability of products, the endurance of products toward temperature and chemicalsubstances, to know the appreciation of chemistry society (students and lecturers) aboutthe chemistry practical equipment glass which is made of lamp glass waste.The methods employed in this research are making the products, temperatureendurance testing, chemical substances’ endurance testing and appreciation of theproducts testing.The results of the research show that (1) the process of making chemistrypractical equipments from lamp glass waste consist of five steps (sorting the lamp glass,cleaning lamp glass, making the models, glassblowing and testing products), (2) theproducts include tube, baker glass, volumetric glass, pipette, flask volumetric,erlenmeyer, graduate pipette. (3) based on the temperature testing, in which thetemperature is up to 1800 C the products are good, and based on the chemical substancetesting, which is 12 M of acid and base, the products also are good. (4) based on thequestionnaires revealing the appreciation of chemical society about performance andutility of the products, the average score of performance is 9.7 (X=9.7). It means theperformance of products is sufficient. The average score of utilizing the products is 8.5(X=8.5).Keywords: lamp glass waste, chemistry equipments glass, chemistry learning